A Juridico-Philosophical Examination of the Death Penalty within the Framework of Legal Philosophy - A, Annisa; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The death penalty remains one of the most controversial forms of criminal punishment within Indonesia’s legal system, provoking longstanding debates from both juridical and philosophical perspectives. On one hand, the state continues to uphold capital punishment as an instrument to maintain public order and provide a deterrent effect against perpetrators of extraordinary crimes. On the other hand, there are views that regard the death penalty as contradictory to humanitarian values and the fundamental human right to life. This study aims to analyze the regulation of the death penalty in Indonesia’s positive law and to examine its existence from the perspective of legal philosophy, particularly through the lenses of utilitarianism, retributivism, and humanism. This research employs a normative juridical method with a statute approach and a conceptual approach. The data were obtained through an analysis of relevant statutory provisions, such as the Indonesian Criminal Code (KUHP), Law No. 39 of 1999 concerning Human Rights, and judicial decisions related to the implementation of capital punishment in Indonesia. The results indicate that the regulation of the death penalty in Indonesia has undergone a paradigm shift toward a more humanistic approach, as reflected in the 2023 Criminal Code, which provides a ten-year probationary period for death row inmates. From a philosophical standpoint, capital punishment can be justified within utilitarian and retributive frameworks as long as it serves to protect society and uphold justice. However, the humanist view rejects its existence, emphasizing that the right to life is non-derogable and cannot be taken away by the state. Therefore, the existence of the death penalty in Indonesia reflects an ongoing effort to balance justice, utility, and humanity.